Isoxazolium N-ylides and 1-oxa-5-azahexa-1,3,5-trienes on the way from isoxazoles to 2H-1,3-oxazines - Khlebnikov, Alexander F.; Novikov, Mikhail S.; Gorbunova, Yelizaveta G.; Galenko, Ekaterina E.; Mikhailov, Kirill I.; Pakalnis, Viktoriia V.; Avdontceva, Margarita S. (Beilstein Journal of Organic Chemistry, 2014)
Theoretical and experimental studies of the reaction of isoxazoles with diazo compounds show that the formation of 2H-1,3-oxazines proceeds via the formation of (3Z)-1-oxa-5-azahexa-1,3,5-trienes which undergo a 6π-cyclization. The stationary points corresponding to the probable reaction intermediates, isoxazolium N-ylides, were located by DFT calculations at the B3LYP/6-31G(d) level only for derivatives without a substituent in position 3 of the isoxazole ring. These isoxazolium N-ylides are thermodynamically and kinetically very unstable. According to the calculations and experimental results 2H-1,3-oxazines are usually more thermodynamically stable than the corresponding open-chain isomers, (3Z)-1-oxa-5-azahexa-1,3,5-trienes. The exception are oxaazahexatrienes derived from 5-alkoxyisoxazoles, which are thermodynamically more stable than the corresponding 2H-1,3-oxazines. Therefore, the reaction of diazo esters with 5-alkoxyisoxazoles is a good approach to 1,4-di(alkoxycarbonyl)-2-azabuta-1,3-dienes. The reaction conditions for the preparation of aryl- and halogen-substituted 2H-1,3-oxazines and 1,4-di(alkoxycarbonyl)-2-azabuta-1,3-dienes from isoxazoles were investigated.
Keywords: diazo esters; isoxazoles; isoxazolium N-ylides; 2-azabuta-1,3-dienes; 2H-1,3-oxazines